MENINGKATKAN KEMAMPUAN MEMBUAT BUNGA DARI STOCKING MELALUI PEMBELAJARAN INDIVIDUAL BAGI ANAK TUNAGRAHITA RINGAN KELAS VII DI SLB YPAC SUMBAR - Ira Yunita (Universitas Negeri Padang, 2016)
IraYunita(2016): Improving Skills to Make Flowers of Stocking Through Individual Learning for Children Tunagrahita Lightweight Class VII in SLB YPAC SUMBAR . Abstract: This research is motivated by the problems of a child with mild mental retardation X class VII can not make flowers skills of stocking. After the assessment of the 17 steps for stocking the interest of the child can only make a two-step.This research uses experimental research methods with Single Subject Research (SSR), with ABA design and technical analysis of the data using visual analysis graphic.These results indicate that the ability to make a stocking rate of increase after a given intervention through individual learning. Baseline conditions were conducted during five observations child gets a score of 17.76%%, on the condition of intervention as much as nine times the observation of the child's ability is increasing and the highest score obtained by children is 94.11%. While the baseline condition both held six times and the highest score is 97.05%. Thus the hypothesis proposed previously acceptable, meaning that the child's ability mild mental retardation X can be increased through individual learning . Keywords:Individualized Learning.Mind Mental Retardation Children.Flower skills